Consideration of Trade-offs Regarding COVID-19 Containment Measures in the United States: Implications for Canada - Mayvis Rebeira; Eric Nauenberg (McMaster University Library Press, 2023)
The economic stimulus package in the United States, which totalled US$2.48 trillion, was designed to soften the economic impact of sweeping containment measures including shelter-in-place orders that were put in place to control the COVID-19 pandemic. In health care, interventions are rarely justified simply in terms of the number of lives saved, but also in terms of a myriad of other trade-off factors including value-for-money or cost-effectiveness. The data suggest the incremental costs per life-year gained related to the lockdown can span a wide range, depending on the baseline number of deaths in the absence of any containment measures. The results show that, in the United States, under no scenario for life-years gained does the stimulus package compare favourably to other health care interventions that have had favourable cost-effectiveness profiles. However, when comparing value-of-statistical-life-year threshold measures used in other sectors, it is plausible that the stimulus package could be viewed more favourably in the United States. In Canada, a similar analysis could have been possible if age-sex mortality and other data used for containment strategy decisions were made available as the pandemic unfolded. Le plan de relance économique des États-Unis, d'un montant de 2,48 billions de dollars, avait été conçu pour atténuer l'impact économique des mesures d'endiguement radicales, y compris les ordres de confinement, qui ont été mises en place pour contrôler la pandémie du virus COVID-19. Dans le secteur des soins de santé, les interventions sont rarement justifiées par le seul nombre de vies sauvées, mais aussi par une myriade d'autres facteurs de compromis, notamment le rapport qualité-prix ou le rapport coût-efficacité. Les données suggèrent que les coûts supplémentaires par année de vie gagnée liés au confinement peuvent varier considérablement en fonction du nombre de décès de référence en l'absence de toute mesure d'endiguement. Nos résultats montrent qu'aux États-Unis, le plan de relance ne soutient pas la comparaison avec d'autres interventions de soins de santé ayant un profil coût-efficacité favorable, quel que soit le scénario envisagé pour les années de vie gagnées. Toutefois, le plan de relance peut être considéré plus favorablement si l'on utilise les mesures de seuil de la valeur statistique de l'année de vie d'autres secteurs. Au Canada, une analyse similaire aurait pu être réalisée si les données de mortalité par âge et par sexe et d'autres données utilisées pour les décisions relatives à la stratégie d'endiguement avaient été disponibles au fur et à mesure du déroulement de la pandémie.